2020
DOI: 10.3390/app10155280
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Actual Power and EMF Exposure from Base Stations in a Commercial 5G Network

Abstract: In this work, monitoring of the transmit power for several base stations operating in a live 5G network (Telstra, Australia) was conducted with the purpose of analyzing the radio frequency (RF) electromagnetic field (EMF) exposure levels. The base stations made use of state-of-the-art massive MIMO antennas utilizing beamforming in order to optimize the signal strength at the user’s device. In order to characterize the actual EMF exposure from 5G base stations, knowledge of the amount of power dynamically alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 6 publications
3
34
0
Order By: Relevance
“…According to Thors et al [2017], the 95th percentile of power transmitted per beam is 7–22% of the theoretical maximum. A study by Colombi et al [2020] showed that all base stations operated at a cell‐wide power level of less than 2.5% of the maximum.…”
Section: Discussionmentioning
confidence: 99%
“…According to Thors et al [2017], the 95th percentile of power transmitted per beam is 7–22% of the theoretical maximum. A study by Colombi et al [2020] showed that all base stations operated at a cell‐wide power level of less than 2.5% of the maximum.…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible to use lower values of K in the analysis, but according to the discussion at the beginning of this section, a smaller number of K would lead to a network that is not fully loaded; similar considerations are also reported in the discussion section of [20].…”
Section: Influence Of the System Parameters On The Q-nappmentioning
confidence: 64%
“…A value of NAPP of 0.1 in a specific direction means that during the T A the BS array would radiate in that direction only a tenth of the power it would radiate when focusing its beam using the maximum gain 100% of the time. This quantity is similar to the parameter G avg , introduced in [20], which is an average gain, obtained "experimentally", by means of the analysis of the information collected by the 5G BSs operation for 24 h over a weekday.…”
Section: Normalized Average Power Patternmentioning
confidence: 73%
See 1 more Smart Citation
“…Note that the input power and the maximum gain given in Table 1 indicates the maximum power transmission from a BS, i.e., the full traffic case considered for a BS installation compliance assessment based on the extrapolation approach [10]- [13]. This input power of 50 dBm is also the same as one used in simulation [32] and similar to one used in measurement study of 53 dBm [33], respectively. A constant side lobe level of -30 dB stems from the antenna model defined in the 3rd Generation Partnership Project (3GPP) channel report [34].…”
Section: ) Simulation Scenariosmentioning
confidence: 99%